Mestre Sabú: memória social e práticas culturais da capoeira em Goiás - Tucunduva, Tatiana (2015)
This research is linked to the research line Culture, Representation and symbolic practices, the Graduate Program in Sociology at the Federal University of Goiás Our analysis area is social memory and cultural heritage, passing by theme: Capoeira in Goiás, in their manifestations symbolic, aesthetic and its power of resistance and social change in the practice of Master Sabu - the pioneer of capoeira in the state. And it is this pioneering spirit that we have to analyze the narratives of Master Sabu through analytical categories that permeated the social memory, life courses, office and ways of doing. As well as, by understanding the social meanings, cultural and symbolic of Capoeira Angola Master Sabu, identification of know-how in Capoeira and its relationship with the instruments it produces, highlighting the challenges, opportunities and social impacts of this work to society Goiânia. The research method was based on oral history, helping us to deal with the production of our own sources, and the living history giving meaning to social life of the deponent. The relevance of this research is to contribute to the debate on the importance of recognizing each knowledge of capoeira masters, contributing mainly to each and every one are recognized and respected from their families by governments.